The Impact of Government Actions and Risk Perception on the Promotion of Self-Protective Behaviors During the COVID-19 Pandemic - Alvarez-Galvez, Javier; Anastasiou, Andreas; Lamnisos, Demetris; Constantinou, Marios; Nicolaou, Christiana; Papacostas, Savvas S.; Vasiliou, Vasilis S.; McHugh, Louise; Lubenko, Jelena; Ruiz, Francisco J.; Paez-Blarrina, Marisa; Montesinos, Francisco; et al. (My University, 2022)
We aim to understand the factors that drive citizens of different countries adhere to recommended self-protective behaviors during the COVID-19 pandemic. Survey data obtained through the COVID Impact project was used. We combined previous evidence and change-point detection analysis to establish variations in self-protective behaviors across participating countries whose effect was then assessed by means of interrupted series analysis. A high level of compliance with health and governmental authorities’ recommendations were generally observed in all countries. The level of stress decreased near the period when countries such as Cyprus, Greece or the United Kingdom relaxed their prevention behavior recommendations. However, this relaxation of behaviors did not occur in countries such as Germany, Ireland or the United States. When the daily number of recorded COVID-19 cases decreased, people relaxed their protective behaviors (Cyprus, Greece, Ireland), although the opposite trend was observed in Switzerland. COVID-19 self-protective behavior following has been heterogeneous across countries examined. Our findings show that there is probably no single winning strategy for exiting future health crises, as similar interventions, aimed to promote self-protective behaviors, may be received differently depending on the singular population groups and on the specific geographical context in which they are implemented.
Keywords: interrupted time series; COVID-19; health behaviors; self-protective behaviors; change-point detection analysis